Pengaruh Kepemimpinan Transformasional pada Intensi Karyawan Keluar dari Perusahaan - Sumarita Sumarita; Muzakki Muzakki (Universitas Prasetiya Mulya, 2023)
This study aims to investigate the effect of transformational leadership on turnover intention. Then, to test the influence through the mediating role of affective commitment. The method used in this study is a quantitative study with a respondent level of 160 employees from a total population of 255 employees in various divisions such as Accounting, Operations, Marketing and Sales, Recruitment, Human Capital, Treasury, IT Management, and Support. Partial least squares (PLS) were used in this study as a data analysis technique to test the hypothesis. The findings of this study reveal that transformational leadership is proven to have a negative and significant effect on employee turnover intention. Then, affective commitment is demonstrated to mediate the relationship between transformational leadership and employee turnover intention. Practical implications and research recommendations are discussed in this study.